A Cartografia temática aplicada como instrumento de análise e síntese no estudo da qualidade de vida urbana : o caso da cidade de Birigui-SP - Gomes, Márcio Fernando (2011)
From the second half of the twentieth century Brazil is going through an intense and accelerated process of urbanization. Urban sprawl and lack of adequate planning led to a deterioration of cities, environmental and social impacts that affect directly the quality of life of city dwellers. From this question, this research discusses the quality of life in the city of Birigui - SP. The central objective of the work is to develop maps for analysis, correlation and synthesis in order to study the quality of urban life in the city of Birigui - SP. To assess the quality of urban life were considered the following indicators: water supply, sanitation, garbage collection, paved roads, the public health, public educational institutions, public transportation, vegetation, thermal comfort and a risk of flooding. Thematic maps allow the identification of areas with higher and lower quality of life as well as inequality in intra-urban space. Overall, the results show that the surrounding areas have compromised the quality of life due to poor infrastructure and urban services, ie the social vulnerabilities, however in the central areas characterized by heavy use and land cover are the natural vulnerabilities that present the most aggravating situations for quality life.